2009
DOI: 10.2298/pif0902123m
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of azadirachtin (NeemAzal-T/S) in controlling pear psylla (Cacopsylla pyri) and European red mite (Panonychus ulmi)

Abstract: SUMMARYHere we present the results of field trials conducted in Serbia to evaluate the effectiveness of a neem-based product, NeemAzal-T/S (containing azadirachtin-A as its active ingredient in the form of an emulsifiable concentrate) against pear psylla (Cacopsylla pyri) and European red mite (Panonychus ulmi).Efficacy evaluation against C. pyri was carried out in a commercial pear orchard of the Williams pear cultivar, located at Borkovac (Ruma). The insecticides were applied at BBCH 09 pear growth stage, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Thus, organic molecules of botanical origin may offer a safe source of compounds for pest management, being environmentally friendly, and an excellent alternative to persistent synthetic insecticides (Biondi et al, 2006). Neem seed extract active ingredient azadiractin 1%, acts as antifeeding, deterrent and growth inhibitor against a number of insects and mites including tomato leaf miner (Marčić et al, 2009;Koul et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, organic molecules of botanical origin may offer a safe source of compounds for pest management, being environmentally friendly, and an excellent alternative to persistent synthetic insecticides (Biondi et al, 2006). Neem seed extract active ingredient azadiractin 1%, acts as antifeeding, deterrent and growth inhibitor against a number of insects and mites including tomato leaf miner (Marčić et al, 2009;Koul et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with T1 (Table 3), T2 (69%) and T3 (54%) had the lower efficiency in both observed years In the Czech Republic, Kocourek and Stara (2006) found that the efficiency of the tested preparations was also different from year to year and that it also differed in the application dates from 92 -100% for Vertimec, which was also used in our study as a part of T1 and T2. In a study conducted in Serbia (Maričić et al, 2009), diflubenzuron achieved the efficiency of 59%. It explains our efficient results for T1 from 84-95%, because each active ingredient in this treatment had its own different effectiveness, which also depends on the other abiotic factors (the time of application, year, etc.).…”
Section: Resultsmentioning
confidence: 98%
“…It is the main pest of melons, technical plants, and horticulture, ornamental trees. More than 150 species of spiders have been reported as the main pests of crops around the world [8,9] . According to other scientists, the apple red mite (Panonychus ulmi Koch) is found in almost all agricultural areas of the world, and phytophagous mites are more plantrelated than all other mites [10] .…”
Section: Introductionmentioning
confidence: 99%